Expressão do gene Glipican 3 (Gpc3) no urotélio da bexiga de ratos expostos ao diuron (3-(3,4-dichlorophenyl)-1,1-dimethylurea) por 7 dias e 20 semanas - Gomide, Lígia Maria Micai [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Diuron (3-(3,4-dichlorophenyl)-1,1-dimethylurea) is a substituted urea herbicide widely used in crops of sugar cane, cotton and soybeans. In 1997, this agent has been classified by the United States Environmental Protection Agency as known/likely human carcinogen because it induced tumors in the urinary bladder and renal pelvis of rats, and breast and skin of mice exposed to 2500 ppm for feed for two years. A previous study from our group demonstrated dose-response relationship in the gene expression profile associated with severe necrosis on bladder urothelium and increased incidence of simple hyperplasia in male Wistar rats treated with different concentrations of diuron for 20 weeks. To check how early the molecular changes occurs, rats were fed for 7 days with diets containing diuron at 0, 125, 500 or 2500 ppm. The main observations recorded were urothelium ultrastructural alterations and disruptions of molecular pathways associated with cell-cell interaction and the tissue organization maintenance. Particularly, the gene Glypican 3 (Gpc3), a surface proteoglycan related to cellular adhesion and apoptosis induction, was down regulated on urothelium exposed to 2500ppm diuron for 7 days and 20 weeks. The aim of this study was validate by quantitative RT-PCR real time, the reduced Gpc3 gene expression in epithelial cells of the urinary bladder of male Wistar rats treated with different concentrations of diuron for 7 days and 20 weeks. The endogenous control of the quantitative PCR real time technique was the β-actin gene and the target was the gene Gpc3. The relative quantification (RQ) was obtained by the method of relative quantification 2-ΔΔCt . Animals exposed to diuron for 7 days or for 20 weeks presented reduction of Gpc3 gene expression compared to the control group. This reduction was statistically significant only for the 7 days study. Moreover, by comparing animals exposed for 7 days with the exposed for 20 weeks, it was ...

O diuron (3-(3,4-dichlorophenyl)-1,1-dimethylurea) é um herbicida derivado da uréia amplamente usado em culturas de cana, algodão e soja. Em 1997, este agente foi classificado pela United States Enviromental Protection Agency como “provável cancerígeno para a espécie humana”, pois induziu tumores na bexiga e pelve renal de ratos, e na pele e mama de camundongos, expostos pela ração a 2500 ppm do produto durante dois anos. Estudo prévio de nosso grupo demonstrou relação dose-resposta no perfil de expressão gênica, associado a focos de necrose grave do urotélio vesical e aumento da incidência de hiperplasia simples em ratos Wistar machos tratados com diferentes concentrações de diuron durante 20 semanas. Para verificar o quão precoce ocorriam as alterações moleculares, ratos foram alimentados durante 7 dias com rações contendo diuron a 0, 125, 500 ou 2.500 ppm. Entre outras observações, foram registradas alterações ultraestruturais da mucosa e comprometimento de vias moleculares associadas à interação célula-célula e à manutenção da organização tecidual. Particularmente, o gene Glipican 3 (Gpc3), um proteoglicano de superfície envolvido na adesão celular e indução de apoptose, apresentou expressão diminuída após 7 dias e 20 semanas de exposição a 2500ppm de diuron. O objetivo do presente estudo foi validar, por RT-PCR quantitativa em tempo real, a redução de expressão do gene Gpc3 em células epiteliais de bexiga urinária de ratos Wistar machos tratados com diferentes concentrações de diuron durante 7 dias e 20 semanas. A técnica de PCR quantitativo em tempo real teve como controle endógeno o gene β-actina e como alvo o gene Gpc3. A quantificação relativa (QR) foi obtida através do método de quantificação relativa 2-ΔΔCt. Foi observada diminuição de expressão do gene Gpc3 nos animais expostos ao diuron por 7 dias ou por 20 semanas, em ...
Keywords: Bexiga - Exame; Expressão gênica; Carcinogenese; Diuron - Estudos experimentais; Herbicidas; Reação em cadeia de polimerase; Gene expression